(under root 5-under root 2)(under root 5+under root 2)
Answers
Answered by
1
Here is your answer
![( \sqrt{5} - \sqrt{2} )( \sqrt{5} + \sqrt{2} ) \\ = ( \sqrt{5} ) {}^{2} - ( \sqrt{2} ) {}^{2} \\ = 5 - 2 \\ = 3 ( \sqrt{5} - \sqrt{2} )( \sqrt{5} + \sqrt{2} ) \\ = ( \sqrt{5} ) {}^{2} - ( \sqrt{2} ) {}^{2} \\ = 5 - 2 \\ = 3](https://tex.z-dn.net/?f=%28+%5Csqrt%7B5%7D++-++%5Csqrt%7B2%7D+%29%28+%5Csqrt%7B5%7D++%2B++%5Csqrt%7B2%7D+%29+%5C%5C++%3D+%28+%5Csqrt%7B5%7D+%29+%7B%7D%5E%7B2%7D++-+%28+%5Csqrt%7B2%7D+%29+%7B%7D%5E%7B2%7D++%5C%5C++%3D+5+-+2+%5C%5C++%3D+3)
Hope it helps you
Hope it helps you
Answered by
0
(√5-√2)(√5+√2)
(√5)²-(√2)²
√25-√4
5-2
=3
(√5)²-(√2)²
√25-√4
5-2
=3
Similar questions